2023
DOI: 10.3390/su15129682
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Factors Affecting Prefabricated Building Quality Based on ISM-BN

Abstract: In recent years, the rise of the domestic industry has boosted the use and popularity of prefabricated buildings. Prefabricated buildings differ significantly from traditional design, construction, and production models. However, due to the short development period of prefabricated buildings in China, the quality management of these new structures is still not mature, resulting in frequent project delays and failure. To improve quality management, this paper aims to establish an evaluation model of factors aff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Mao, Y. and Tuo, X. suggested that The risk awareness of personnel, the application level of information technology, the way the interests of supply chain stakeholders are distributed, the level of government support, and the regulatory ability of enterprises will affect PBSCR according to the analysis of the critical path. This is similar to the 4M1E theory [55,56]. "4M1E" refers to man, machine, material, method, and environment.…”
Section: Discussionmentioning
confidence: 62%
“…Mao, Y. and Tuo, X. suggested that The risk awareness of personnel, the application level of information technology, the way the interests of supply chain stakeholders are distributed, the level of government support, and the regulatory ability of enterprises will affect PBSCR according to the analysis of the critical path. This is similar to the 4M1E theory [55,56]. "4M1E" refers to man, machine, material, method, and environment.…”
Section: Discussionmentioning
confidence: 62%
“…Currently, the entire lifecycle of quality control of steel prefabricated components is essential to ensuring the success of the construction project. The process comprises three primary phases: production, transportation and storage, and on-site construction, each of which employs specific control measures to guarantee the quality and performance of the components [5]. During the production stage, starting with the selection and inspection of raw materials, every phase of the process must be executed precisely, including cutting, forming, welding, and surface treatment, to ensure that the size, shape, and quality of the components meet the design requirements.…”
Section: Introductionmentioning
confidence: 99%
“…Using SEM-SDM, Li et al assessed the safety risk of prefabricated building construction [3]. In an effort to enhance the management of quality for prefabricated buildings, Zhang et al used ISM-BN to establish an evaluation model of the factors influencing the quality of as-assembled structures [4]. Zhang et al used ISM-MICMAC to investigate the relationships between 23 components of prefabricated structures quality management [5].…”
Section: Introduction 1background Of the Studymentioning
confidence: 99%